ANALISIS PENERAPAN AKUNTANSI BIAYA LINGKUNGAN SEBAGAI PERTANGGUNGJAWABAN SOSIAL DI RSI HIDAYATULLAH YOGYAKARTA - Risa Nurwulan Sari; Achmad Tjahjono (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2017)
Environmental cost is also known as the cost of environmental quality. The treatment cost of environmental quality is equal to the cost of environmental quality, so that the cost of environmental quality can be grouped into : environmental prevention costs, environmental detection costs, environmental internal failure costs, and environmental external failure costs. The purpose of this study is to investigate and analyze how firms identify, recognize, measure, assess and present and disclose the environmental cost in the financial statements. This research was conducted at the Hidayatullah Islamic Hospital of Yogyakarta who has had WWTP by using biological method, that is activated sludge. This study is a qualitative research. This study uses primary data and secondary data. Primary data were collected by interview. The results of this study are in the hospital recognizes the environmental costs and presented into a single account with the other similiar cost in the primary financial statement. Environmental cost is measured by the cost incurred (Historial Cost) with the monetary units rupiah. Environmental costs are not disclosed in the notes of the financial statements (CALK), but disclosed in a descriptive report, a report UKL-UPL.